A Qualitative Study on Knowledge, Attitude, and Practice of Nursing Students in the Early Stage of the COVID-19 Epidemic and Inspiration for Nursing Education in Mainland China - Zhou, Houxiu; Zhao, Rongrong; Yang, Yanni (Frontiers in Public Health, 2022)
Background At the beginning of the COVID-19 outbreak, there was a lack of sufficient nursing experience for pneumonia caused by COVID-19. All nursing decisions had to be innovatively made and measures taken by nurses using their existing knowledge and skills. This required nurses to have a solid theoretical understanding of infectious diseases and epidemiology, evidence-based solid practice skills, and problem-solving skills. The COVID outbreak reminded undergraduates to master relevant knowledge and abilities during school study. Methods Qualitative research on knowledge, attitude, and practice (KAP) of the COVID-19 epidemic was conducted using semi-structured interviews among sophomore nursing students in the university. Based on the characteristics of the KAP of nursing students, we analyzed the deficiencies of the knowledge and ability to deal with large-scale public health emergencies in the second-year nursing education. Results A total of 12 subject headings and 41 sublevel headings were identified from three aspects of KAP. The subject headings included knowledge aspect (the origin of the disease, the route of transmission, main symptoms, the epidemiological characteristics of the disease, scientific cognition of information sources), attitude aspect (different emotional experiences, a certain degree of influence, different views on the development trend of the epidemic, support the government's prevention and control strategies), and behavior aspect (do an excellent job in self-protection, help family members to protect, and participate in social anti-epidemic actions). According to this analysis, second-year nursing students have three deficiencies in dealing with large-scale public health emergencies: knowledge of infectious diseases and epidemiology, evidence-based practice skills, and problem- solving ability. Conclusion When students start nursing professional courses, the knowledge of infectious diseases and epidemiology, training of evidence-based practice skills, and problem-solving ability should be strengthened to improve the ability of nursing undergraduates to respond to large-scale public health emergencies after entering the workplace.